Numerization model for calculating irrigation water requirements - Agus Lasse; Ratna Musa; Mas’ud SAR (Jurnal Scientia, 2024)
Water is an important resource in supporting the survival of all living things. The Indonesian government seeks to develop the water sector with the aim of directly influencing the water needs of society through the use of water, especially in agriculture, to meet food needs and encourage regional development. The aim of this research is to calculate irrigation water requirements manually using KP-01 and Cropwat 8.0 software. This research uses the Research and Development (R & D) research method. Data collection techniques in this research were observation, interviews and literature study. Modified Penman climatology analysis was used, with irrigation water requirements derived from KP-01 and Cropwat 8.0 software. The research results show that starting from the second period in September when land preparation begins, the analysis of irrigation water requirements for the rice-paddy-palawija cropping pattern shows that for alternative I, the maximum value of irrigation water requirements is 2.32 L. /second/ha; in alternative II it is 2.00 L/second/ha; and in alternative III it is 1.99 L/second/ha. Using Cropwat 8.0 software, the highest irrigation water requirement value was obtained in February of the third decade of 1.99 L/second/ha, while the smallest maximum irrigation water requirement value was 1.6 L/second/ha in the second period of October.